Association between functional recovery and medication adherence in schizophrenia - Junpei Ishii; Fumitoshi Kodaka; Hisatsugu Miyata; Wataru Yamadera; Hikaru Seto; Hidejiro Higuchi; Yoshiaki Tsuruoka; Masahiro Shigeta (Wiley, 2022)
Abstract Aim Medication adherence is important for achieving functional recovery from schizophrenia and is commonly assessed using the Drug Attitude Inventory‐30 (DAI‐30). Subscales of the DAI‐30, including "awareness of the need for medication," "awareness of the effects of psychiatric drugs," and "impression of medication," have been used to assess medication adherence. To determine which of these subscales are associated with the prognosis of schizophrenia, this study followed patients with schizophrenia to identify the prognosis and examine the subscales related to "recovery." Methods In total, 89 patients were recruited, 78 of whom were registered in the study. After assessing adherence using the DAI‐30, Positive and Negative Syndrome Scale and Global Assessment of Functioning scores were assessed at 0 and 24 week to define the functional prognosis. Results At the end of the 24‐week follow‐up period, 36% of patients showed recovery from schizophrenia. A comparison of subscales revealed that the score for "impression of medication" was significantly higher in the recovery than in the non‐recovery group. Logistic regression analysis identified only the "impression of medication" score as being predictive of recovery. Conclusion The results indicated that among the three DAI‐30 subscales, "impression of medication" was the most closely associated with recovery in patients with schizophrenia.